Semi-automatic engineering and tailoring of high-efficiency Bragg-reflection waveguide samples for quantum photonic applications. (25th January 2018) - Pressl, B; Laiho, K; Chen, H; Günthner, T; Schlager, A; Auchter, S; Suchomel, H; Kamp, M; Höfling, S; Schneider, C; Weihs, G
Abstract: Semiconductor alloys of aluminum gallium arsenide (AlGaAs) exhibit strong second-order optical nonlinearities. This makes them prime candidates for the integration of devices for classical nonlinear optical frequency conversion or photon-pair production, for example, through the parametric down-conversion (PDC) process. Within this material system, Bragg-reflection waveguides (BRW) are a promising platform, but the specifics of the fabrication process and the peculiar optical properties of the alloys require careful engineering. Previously, BRW samples have been mostly derived analytically from design equations using a fixed set of aluminum concentrations. This approach limits the variety and flexibility of the device design. Here, we present a comprehensive guide to the design and analysis of advanced BRW samples and show how to automatize these tasks. Then, nonlinear optimization techniques are employed to tailor the BRW epitaxial structure towards a specific design goal. As a demonstration of our approach, we search for the optimal effective nonlinearity and mode overlap which indicate an improved conversion efficiency or PDC pair production rate. However, the methodology itself is much more versatile as any parameter related to the optical properties of the waveguide, for example the phasematching wavelength or modal dispersion, may be incorporated as design goals. Further, we use the developed tools to gain a reliable insight in the fabrication tolerances and challenges of real-world sample imperfections. One such example is the common thickness gradient along the wafer, which strongly influences the photon-pair rate and spectral properties of the PDC process. Detailed models and a better understanding of the optical properties of a realistic BRW structure are not only useful for investigating current samples, but also provide important feedback for the design and fabrication of potential future turn-key devices.